The Impact of Shared Vision on Leadership, Engagement, Organizational Citizenship and Coaching - Scott N. Taylor (Frontiers Research Topics, 2015)
According to management and psychology courses, as well as legions of consultants in organizational psychology, shared vision in dyads, teams and organizations can fill us with hope and inspire new possibilities, or delude us into following false prophets. However, few research studies have empirically examined the impact of shared vision on key organizational outcomes such as leadership effectiveness, employee engagement, organizational citizenship, coaching and organizational change. As a result, the field of organizational psychology has not yet established a causal pattern of whether, if, and how shared vision helps dyads, teams and organizations function more effectively. The lack of empirical work around shared vision is surprising given its long-standing history in the literature. Bennis and Nanus (1982) showed that distinctive leaders managed attention through vision. The practitioner literature has long proclaimed that vision is a key to change, while Conger and Kanungo (1998) discussed its link to charismatic leadership. Around the same time, positive psychology appeared in the forms of Appreciative Inquiry (Cooperrider, Sorensen, Whitney, & Yaeger, 2000) and Positive Organizational Scholarship (Cameron, Dutton, & Quinn, 2003). In this context, a shared vision or dream became a legitimate antecedent to sustainable change. But again, empirical measurement has been elusive. More recently, shared vision has been the focus of a number of dissertations and quantitative studies building on Intentional Change Theory (ICT) (Boyatzis, 2008) at dyad, team and organization levels of social systems. These studies are beginning to lay the foundations for a systematic body of empirical knowledge about the role of shared vision in an organizational context. For example, we now know that shared vision can activate neural networks that arouse endocrine systems and allow a person to consider the possibilities of a better future (Jack, Boyatzis, Leckie, Passarelli & Khawaja, 2013). Additionally, Boyatzis & Akrivou (2006) have discussed the role of a shared vision as the result of a well-developed set of factors that produce a desired image of the future. Outside of the organizational context, positive visioning has been known to help guide future behavior in sports psychology (Loehr & Schwartz, 2003), medical treatment (Roffe, Schmidt, & Ernst, 2005), musical performance (Meister, Krings, Foltys, Boroojerdi, Muller, Topper, & Thron, 2004), and academic performance (Curry, Snyder, Cook, Ruby, & Rehm, 1997). This Research Topic for Frontiers in Psychology is a collection of 14 original papers examining the role of vision and shared vision on a wide variety of desired dependent variables from leadership effectiveness and executive performance to organizational engagement, citizenship and corporate social responsibility, and how to develop it through coaching.